Answer:
(x - 3)^2 + (y + 1) = 25
Step-by-step explanation:
First find the midpoint of the diameter, because that represents the center of the circle.
-1 + 7
The x-coordinate of the midpoint is xm = ---------- = 3
2
2 - 4
and the y-coordinate is ym = ---------- = -1
2
And so the center of this circle is at (3, -1).
Use the Pythagorean Theorem to determine the square of the radius:
square of radius = 4^2 + (-3)^2 = 16 + 9 = 25
And so the equation of this circle is (x - 3)^2 + (y + 1) = 25
Answer:
2.5 years
Step-by-step explanation:
I = 200 T=200/4000 0.2 = 2.5 years
P= 4000
R = 2% 0.2
T = ?
Answer:
Tn=a + (n-1)d
a= first term = 14
n= This is the term you're looking for... In this case... That's the 73rd term
d=Common difference (since its an AP)
d= second term - first term -- Or 3rd term - 2nd term = 23-14
d=9
T = 14 + (73-1)9
T= 14 + (72)9
T= 14 + 648
T=662.
C
explaination Hsjsksksodhveomgomgzksnnsnsnsnns
Answer:
D
Step-by-step explanation:
Plug in and see.
Check A: Lets plug in (0,3) into y<2/3 x+2.
3<2/3 (0)+2
3<2 is not true so not A
Check C: Lets plug in (3,5) into y<2/3 x+2.
5<2/3 (3)+2
5<2+2
5<4 is not true so not C
Check B: Lets plug in (-3,1) into y<2/3 x+2.
1<2/3 (-3)+2
1<0 is not true so not B
Check D: Lets plug in (1,2) into y<2/3 x+2.
2<2/3 (1)+2
2<2/3+2 is true so D